Problem Based Learning (PBL) Learning Model to Improve Understanding of Pancasila Values of Grade 3 Students of SD N 2 Bantarwuni - Hofisah, Utbah Aminatul; Faridli, Efi Miftah; Rumiyati, Rumiyati (UM Purwokerto Press, 2025)
This study aims to examine the extent to which students' understanding and attitudes towards Pancasila values are improved through the application of the Problem Based Learning (PBL) learning model in class II of SD N 2 Bantarwuni. The method used is Classroom Action Research (CAR) which is implemented in two cycles. The research subjects were 17 students. Data collection techniques include observation, tests, and documentation. The results of the study showed an increase in the average score of students from 75 in the pre-cycle to 82 in cycle I and 89 in cycle II. Based on these results, it can be concluded that the application of the Problem Based Learning (PBL) model has proven effective in improving the understanding of Pancasila values among elementary school students.